Dentistry and the pregnant patient - Ninan, Daniel ([S.l.] : Quintessence Publishing Co, Inc., 2019)
To err on the side of caution, some dentists may hesitate to perform necessary procedures on pregnant patients. However, good oral health is essential to a healthy pregnancy and can help reduce prenatal complications, including preterm delivery and fetal loss. This book serves as an easy-to-use guide to help dentists of all specialties provide safe, effective care for their patients during pregnancy. The book is broken down into chapters on general treatment guidelines, pregnancy-related conditions in each organ system that may impact care, and the safety of the use of common dental drugs, including anesthetics, during pregnancy. With over 50 quick-reference charts and tables and a breakdown of treatment recommendations by trimester, this book is a must-have for any dental office.
Dentistry and the pregnant patient -- Contents -- Preface -- Chapter 1. Perceptions About DentalTreatment DuringPregnancy -- Chapter 2. Considerations for Treating Pregnant Patients -- Chapter 3. Complications and the Impacton Dental Care -- Chapter 4. Procedures and Treatment Guidelines -- Chapter 5. Administration of Drugs During Pregnancy -- Chapter 6. Medications -- Chapter 7. Anesthetic Use -- Appendices -- Index.
Includes bibliographical references and index.
Keywords: Dental care; Pregnant woman